Propuesta para la implementación de un Modelo de Gestión de Mantenimiento en Tropical Paradise Fruits Company - Rodríguez-Castro, Fernando Antonio (Instituto Tecnológico de Costa Rica, 2018)
The project was made in Tropical Paradise Fruits Company, located in San Carlos, where its main activity is the export of frozen pineapple pulp, it also gives the export of pineapple and its processed juice. So, these quality standards and excessive competition in the market, have caused the company to reduce downtime, increase production and ensure that the equipment in the different processes have a high level of reliability and availability. This is where an adequate maintenance management will help comply operational functions as expected. The project aims to improve maintenance management, helping the company with tools that strengthen the planning, programming and execution of maintenance activities, also, integrate other departments to seek solutions together and improve the handling of information through the Implementation of QR codes and databases, helping to continuous improvement. The management model was developed through the AMFE methodology and an evaluation carried out with the Covenin Standard 2500-93, where the most frequent faults presented in the lines were determined and the weak points that were analyzed were analyzed to improve the state of the department. of maintenance. With the respective results, preventive maintenance plans, technical specifications, lubrication protocols and scheduled inspections will be prepared to ensure the operation of the equipment. It was determined that to make the respective improvements, reviewing outsourcing contracts in detail and improving the documentation of information will reduce maintenance costs and improve the useful life of the equipment, with considerable savings for the company.
Proyecto de Graduación (Licenciatura en Mantenimiento Industrial) Instituto Tecnológico de Costa Rica, Escuela de Ingeniería Electromecánica, 2018
Keywords: Mantenimiento; Modelos; Gestión; Programación; Evaluación; Research Subject Categories::TECHNOLOGY::Engineering mechanics